How parents and practitioners experience research without prior consent (deferred consent) for emergency research involving children with life threatening conditions: a mixed method study. Issue 9 (18th September 2015) - Woolfall, Kerry; Frith, Lucy; Gamble, Carrol; Gilbert, Ruth; Mok, Quen; Young, Bridget; ,
Abstract : Objective: Alternatives to prospective informed consent to enable children with life-threatening conditions to be entered into trials of emergency treatments are needed. Across Europe, a process called deferred consent has been developed as an alternative. Little is known about the views and experiences of those with first-hand experience of this controversial consent process. To inform how consent is sought for future paediatric critical care trials, we explored the views and experiences of parents and practitioners involved in the CATheter infections in CHildren (CATCH) trial, which allowed for deferred consent in certain circumstances. Design: Mixed method survey, interview and focus group study. Participants: 275 parents completed a questionnaire; 20 families participated in an interview (18 mothers, 5 fathers). 17 CATCH practitioners participated in one of four focus groups (10 nurses, 3 doctors and 4 clinical trial unit staff). Setting: 12 UK children's hospitals. Results: Some parents were momentarily shocked or angered to discover that their child had or could have been entered into CATCH without their prior consent. Although these feelings resolved after the reasons why consent needed to be deferred were explained and that the CATCH interventions were already used in clinical care. Prior to seeking deferred consent for the first few times, CATCH practitioners were apprehensive, although their feelings abated with experience of talking to parents about CATCH. Parents reported that their decisions about their child's participation in the trial had been voluntary. However, mistiming the deferred consent discussion had caused distress for some. Practitioners and parents supported the use of deferred consent in CATCH and in future trials of interventions already used in clinical care. Conclusions: Our study provides evidence to support the use of deferred consent in paediatric emergency medicine; it also indicates the crucial importance of practitioner communication and appropriate timing of deferred consent discussions.